2012
DOI: 10.4049/jimmunol.1101373
|View full text |Cite
|
Sign up to set email alerts
|

New Insights on OX40 in the Control of T Cell Immunity and Immune Tolerance In Vivo

Abstract: OX40 is a T cell costimulatory molecule that belongs to the TNFR superfamily. In the absence of immune activation, OX40 is selectively expressed by Foxp3+ Tregs, but not by resting conventional T cells. The exact role of OX40 in Treg homeostasis and function remains incompletely defined. Here, we demonstrate that OX40 engagement in vivo in naïve mice induces initial expansion of Foxp3+ Tregs, but the expanded Tregs have poor suppressive function and exhibit features of exhaustion. We also show that OX40 enable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
75
1
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(82 citation statements)
references
References 48 publications
4
75
1
2
Order By: Relevance
“…Our data are in line with the ones of Oppenheim and colleagues (19,20), which showed a direct effect of TNF on Treg cells via its TNFR2, inducing an increase of their proliferation and survival. Regarding OX40, it has been shown that OX40 agonist administration in- The Journal of Immunologyduced an increase of Treg cell proliferation and that OX40-deficient Treg cells had reduced survival capacity in inflamed tissues (33,34). Interestingly, blocking both TNF and OX40L in ins-HA mice did not fully inhibit the Teff→Treg boost (data not shown), suggesting that other molecules were involved.…”
Section: Molecular Mechanisms Of the Teff→treg Boostmentioning
confidence: 95%
“…Our data are in line with the ones of Oppenheim and colleagues (19,20), which showed a direct effect of TNF on Treg cells via its TNFR2, inducing an increase of their proliferation and survival. Regarding OX40, it has been shown that OX40 agonist administration in- The Journal of Immunologyduced an increase of Treg cell proliferation and that OX40-deficient Treg cells had reduced survival capacity in inflamed tissues (33,34). Interestingly, blocking both TNF and OX40L in ins-HA mice did not fully inhibit the Teff→Treg boost (data not shown), suggesting that other molecules were involved.…”
Section: Molecular Mechanisms Of the Teff→treg Boostmentioning
confidence: 95%
“…Notably, our findings share similarities with other studies using Ox40 agonist treatments. Ox40 agonist treatment exacerbated models of experimental uveitis (67,68) and promoted inflammatory lung pathology in B6 mice (69). However, in other models, the diseasepromoting effects of Ox40 agonism depended upon age and disease severity of the animals (e.g., in experimental autoimmune encephalitis and type 1 diabetes, in which treatment promoted disease during later or effector phases but protected from disease when provided during early or priming phases) (70)(71)(72).…”
Section: Il-21r-fc Treatment In the Mrl-fasmentioning
confidence: 99%
“…Unlike 4C12, the fusion protein induced the proliferation of CD4 + Foxp3 + Tregs in vitro and could be repeatedly administered to maintain elevated Treg levels in vivo. Although there have been studies reporting methods that expand endogenous Tregs (22)(23)(24), to our knowledge we provide the first description of a molecule and method to sustain prolonged in vivo Treg expansion. The TL1A-Ig fusion protein may provide both ex vivo and in vivo strategies for Tregbased therapies in humans.…”
Section: S Everal Members Of the Tnf Superfamily Expressed By T Cellsmentioning
confidence: 99%